Dance behaviour in cockatoos: Implications for cognitive processes and welfare - Natasha Lubke; Suzanne D.E. Held; Melanie Massaro; Rafael Freire (PLoS ONE, 2025)
Parrots (Aves, Psittaciformes) in captivity have been reported to show dance behaviour in response to music, which may involve complex cognitive processes including imitation, vocal learning and entrainment. Dance behaviour in parrots may be indicative of a positive welfare state raising the possibility of using music as a form of environmental enrichment. In this study we studied dance behaviour in cockatoos (Cacatuidae) through an online video study and a playback experiment. First, we identified and defined cockatoo dance movements to music from videos posted on social media to reveal the extent of this behaviour in different species. Second, to test whether music elicited dance behaviour we conducted a preliminary playback experiment on captive cockatoos, whereby birds were presented with periods of music playback, no audio playback and an audio podcast. From 45 online videos representing five different cockatoo species we identified and described 17 new dance movements. We also found 17 rare movements observed in only one bird and not previously reported in the literature, which in many cases consisted of combinations of different movements. A cluster analysis indicated that inter-species similarities in dance movements were not related to phylogenetic relatedness. In the playback study, which involved zoo-housed male-female pairs of three species of cockatoos, all birds in all treatments showed dance behaviour but there was no significant effect of treatment on the probability of showing dancing behaviour. We conclude that dance behaviour in cockatoos is composed of a wide range of different movements and further research would be beneficial to determine if music can trigger dance in captive birds and serve as a form of environmental enrichment.